Suporte social e qualidade de vida de pacientes com diabetes mellitus tipo 1 - Bezerra, Fabrícia Salvador (2015)
Introduction:Type 1 diabetes mellitus is a prevalent disease with high morbidity, and mortality where their care and treatment usually comes with high demand for patients, family, careers, social network, and health care system. Few studies accessing social network and quality of life in patients with diabetes were previously conducted. However those studies were mainly in type 2 diabetic patients, and those evaluating Brazilian population were scarce. Objective: To evaluate social support perception and degree of suffering of Brazilian patients living with T1DM. Method: This is a cross-sectional analytical study, where 105 patients at least 13 years-old with medical diagnosis of T1DM, attending Diabetes Centers in the city of Fortaleza, Ceará were included. Patients with mental disorders, vision or hearing impairment, as well as pregnant women or functionally illiterate were excluded. All of 105 patients performed clinical evaluation, including an application of Social Support Perception Scales (EPSS) and Problem Areas in Diabetes Scale (PAID) validated in Brazil (BPAID), as well as a semi-structured questionnaire including socioeconomic variables: sex, age, family income, socioeconomic class, schooling, presence of family conflicts; clinical and epidemiological variables: time of diagnosis of the T1DM, tobacco smoking, alcohol consumption, physical activity, body mass index; and variables related to foot self-care, and a foot examination. Results: Of those 105 participants, the average of age was 27.4 years (+ 11.5); 43.8% (n=46) were between 13-23 years; 53.3% (n=56) were women; 56.8% (n=58) earn 2-3 minimum wages, and 40.9% (n=43) come from middle socioeconomic class; the average of the time of T1DM diagnosis was 13.2 years (±10,3), average age of the patients for diagnosis was 14.3 years (±7,3); 52.4% (n=55) didn’t exercise; average value of glycated hemoglobin 8.7% (±1.9); 50.5% (n=53) had calluses; dry skin, fissures or cracks 47.6% (n=50); interdigital mycosis 5.7% (n=6); onychomycosis 18.1%; bone deformity 7.6% (n=8); amputation 2.9% (n=3). Medians of EPSS and B-PAID score were 3.3±0.5 and 22.5±20.9 points, which indicates a good perception of social support and few suffer in living with T1DM, not reflecting or interfering in daily activities and social relationship, since the association between the two scales was significant (p=0.027). It was observed the association between scales was significant. Association between EPSS and living alone (p=0.000), as well as with participants’ socioeconomic status (p=0.049) were also observed; Moreover B-PAID score was associated with the duration of T1DM (p=0.001), and with adherence to insulin treatment (p=0.045). Conclusion: Despite the complexity and proper demands of T1DM, it was not observed major compromise in quality of life related to live/or live with T1DM, which could be associated to the good social support perception by them.